STRATEGI PEMERIKSAAN LABORATORIUM ANTIHIV - Woro Umi Ratih (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2012)
Abstract: Human Immunodeficiency Virus (HIV) infection has increased significantly in recentyears. The virus continues to spread in all the countries. There are some strategies and programsto control HIV infection by activities carried out individually or groups. HIV testing technologiesare needed for use in diagnostic testing. Data from diagnostic testing may be used as a source ofsurveillance information. Rapid Diagnostic Test (RDT) and ELISA with various reagents are thecurrent diagnostic testing procedures. It is important to select reagents to get the good results.Keywords : HIV, testing, diagnostic